Perancangan Sistem Pembelajaran Sejarah Islam di Indonesia Berbasis Android dengan Metode Prototype - Sutanto, Arif Sutanto; Djamaludin, Djamaludin; Nurhafsari, Asri (JURNAL ILMIAH FAKULTAS TEKNIK, 2024)
Background: Mobile technology is a technology that is widely used by the people of Indonesia as a communication tool to connect with each other, both in the field of Business and also as a learning medium. Mobile technology is different from personal computers or computer devices a striking difference is in the size and ability to get information. Islam is a religion brought by the Prophet Muhammad saw in the 6th century, then spread throughout the world including Indonesia.  In Indonesia the religion of Islam entered around the 13th century, but there are some who argue that islam already existed in Indonesia around the 7th century.  Through this application, knowledge of Islamic history information ranging from sabang to merauke, starting from the entry to the spread of Islam in Indonesia will be explained in full. By utilizing technology in an application that can make it easier for all smartphone users to learn about the history of Islam in Indonesia. Keywords: History, Android, Technology, Information, Apps, Islam Religion